1994
DOI: 10.1172/jci117588
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis stimulates nonlysosomal, energy-dependent proteolysis and increases ubiquitin mRNA levels in rat skeletal muscle.

Abstract: We tested the role of different intracellular proteolytic pathways in sepsis-induced muscle proteolysis. Sepsis was induced in rats by cecal ligation and puncture; controls were sham operated. Total and myofibrillar proteolysis was determined in incubated extensor digitorum longus muscles as release of tyrosine and 3-methylhistidine, respectively. Lysosomal proteolysis was assessed by using the lysosomotropic agents NH4Cl, chloroquine, leupeptin, and methylamine. Ca2"-dependent proteolysis was determined in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
220
3
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(246 citation statements)
references
References 44 publications
(46 reference statements)
19
220
3
4
Order By: Relevance
“…However, this mechanism is opposite to that induced by glucocorticoids, which have been shown (Du et al, 2000), at least in L6 muscle cells, to induce expression of the C3 proteasome subunit by antagonising interaction of NF-kB with the response element in the promoter region. Studies on protein degradation during sepsis, which is also mediated through the ubiquitin -proteasome pathway (Tiao et al, 1994), showed that NF-kB is increased at early time points (4 h), but decreased at later time points (16 h) (Penner et al, 2001). Which of these changes in NF-kB expression are responsible for the increased muscle protein degradation is not known, but the glucocorticoid receptor antagonist RU38486 increases NF-kB, suggesting that the decreased expression is due to glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism is opposite to that induced by glucocorticoids, which have been shown (Du et al, 2000), at least in L6 muscle cells, to induce expression of the C3 proteasome subunit by antagonising interaction of NF-kB with the response element in the promoter region. Studies on protein degradation during sepsis, which is also mediated through the ubiquitin -proteasome pathway (Tiao et al, 1994), showed that NF-kB is increased at early time points (4 h), but decreased at later time points (16 h) (Penner et al, 2001). Which of these changes in NF-kB expression are responsible for the increased muscle protein degradation is not known, but the glucocorticoid receptor antagonist RU38486 increases NF-kB, suggesting that the decreased expression is due to glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as E3 ligases, destacam-se a Atrogin-1/ MAFbx, MuRF1 e E3a, que são altamente expressas na musculatura esquelética e aumentam consideravelmente sua expressão em estados de atrofia, como jejum, sepsis, câncer, diabetes e AIDS. [36][37][38][39] Schulze e colaboradores recentemente (2005) demonstraram que a E3 ligase Atrogin-1/MAFbx está com sua expressão aumentada no tecido muscular esquelético de camundongos com disfunção ventricular decorrente de infarto do miocárdio.…”
Section: Alterações Molecularesunclassified
“…Unfortunately, very little is known about E3s in skeletal muscle, although thel4-kDa E2 is one of the major mammalian E2s that best supports E3-dependent conjugate formation and protein breakdown [20]. Gonen et al [16] [40,41]. In contrast, a decrease in ubiquitin-conjugates was observed during corticosterone treatment [4].…”
Section: Ubiquitin-protein Ligases E3smentioning
confidence: 99%
“…The reasons for such discrepancies are unclear, although it is conceivable that in some cases the changes in the levels of ubiquitin-conjugates may result from alteration in their rates of degradation. It has been observed that ubiquitylated proteins accumulate preferentially in the myofibrillar fraction [50], although others report conflicting findings [41]. Therefore, the proteins that are preferentially ubiquitylated in skeletal muscle remain to be identified.…”
Section: Ubiquitin-protein Ligases E3smentioning
confidence: 99%
See 1 more Smart Citation